ANALISIS PENERAPAN LITERASI BUDAYA DAN KEWARGAAN DALAM MATA PELAJARAN PENDIDIKAN PANCASILA DI KELAS 2 SD SUPRIYADI - Fitriyana, Anifatul; Nuvitalia, Duwi; Setyaningsih, Ariani Nur; Nugroho, Aryo Andri (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2024)
This research aims to obtain information regarding the application of cultural and civic literacy to students in the Pancasila Education subject at Supriyadi Elementary School, especially class 2B. In learning Pancasila education, cultural and civic literacy has a very important role because cultural and civic literacy involves understanding local, national and global culture, as well as understanding the rights and obligations of being an active and responsible citizen. To be able to create and develop cultural literacy in learning Pancasila education, teachers need to create learning conditions that involve student activity. The method used in this research is field observation and interviews. Data was obtained through observation and interviews and then concluded. Data processing and analysis was carried out qualitatively with descriptive explanations. From the research results, it is known that the implementation of cultural and civic literacy in class 2B Pancasila education subjects at Supriyadi Elementary School has been carried out well. The implementation of cultural and civic literacy in Pancasila Education subjects is concluded from 4 indicators of cultural and civic literacy, namely: 1) understanding the complexity of culture and citizenship, 2) knowing one's own culture, 3) knowing the obligations of citizenship, 4) Cultural Care that has been implemented. divided into 5 categories of activities, namely familiarization activities, development activities, learning activities, activities to optimize the development of students' rights and obligations, and enrichment activities.